Product Management Strategies for AI Integration in American Higher Education (Journal of Science & Technology, 2023)
The adoption of Artificial Intelligence (AI) in American Higher Education is becoming more and more viewed as a strategic direction to improving learning outcomes and endeavors of institutions. However, the actualisation of AI technologies call for proper management of products so as to avoid unsuccessful deployment. This article aims to examine the function of product management with reference to the implementation of AI in the context of higher education considering the main problem and specifics of working with it for the educational institution. The research focuses on the identification of the current global practices in the implementation of AI, practices of developing AI products, management of such solutions in higher education institutions and the identification of general practices and trends in the context of AI in general. Based on the examples of AI projects in education this article defines key lessons on how to approach AI projects: · Communication with the stakeholders · Systems’ development in accordance with the agile methodologies and iterative approach. The identified challenges point to the need to integrate AI products to the overall institutional objectives, create cross-sector ties between academic and administrative divisions and consider the issues of AI solutions’ scalability and future-proofing. By applying the strategy set by Icomp, the product managers and educational leaders of higher education institutions will find guidance in integrating AI into their institutions. Several of the approaches presented in this article are intended to help address main challenges, unlock AI’s potential, and foster innovation in learning environment.